The Effect of University Organizational Climate on Lecturer Productive Behaviour in Private Universities in East Java, Indonesia - Mayastuti,; Suhariadi, Fendy; Yulianti, Praptini (Technium Business and Management, 2022)
This study shows evidence that the direct influence, including organizational climate, has a significant effect on the productive behavior of lecturers in private universities in East Java, Indonesia. This study uses a model concept that emphasizes the individual level, where individual factors have an essential role in an organization. Organizational sustainability is found in individuals in the organization, especially those who have good behavior and are supported by organizational climate. Another factor is job satisfaction for productive behavior; it will strongly influence and make a habit of doing constructive behavior. This research method uses a survey in which the sample is taken from the population with a questionnaire as a tool in the primary data collection. The unit of analysis is lecturers from private universities in East Java, Indonesia. On the other hand, this research can also be regarded as explanatory research that examines and discusses the effect of organizational climate variables and job satisfaction on productive behavior in private university lecturers in East Java, Indonesia. Based on the statistical calculations using the structural equation model (SEM) analysis technique, this study shows that the path coefficient value from organizational climate to job satisfaction is 0.384. strong influence. The results of data analysis using a structural equation model show that there is a path coefficient value from organizational climate to productive behavior with a value of 0.207; the importance of this path coefficient has a positive direction which explains that the more vigorous or higher the value of organizational climate is owned and felt by private university lecturers in East Java. The conclusion is that private universities in East Java have their peculiarities in maintaining the institution in the face of uncertain fluctuations or changes that are not easily predictable. Private universities in East Java have a relatively large number of institutes, high schools, polytechnics, and universities. In the face of various uncertain conditions, it is necessary to have an effort that emphasizes more productive behavior. The application of constructive behavior needs support and some theories on which to base it.